2022
DOI: 10.1371/journal.pone.0268866
|View full text |Cite
|
Sign up to set email alerts
|

The health impacts of the COVID-19 pandemic on adults who experience imprisonment globally: A mixed methods systematic review

Abstract: Background The prison setting and health status of people who experience imprisonment increase the risks of COVID-19 infection and sequelae, and other health impacts of the COVID-19 pandemic. Objectives To conduct a mixed methods systematic review on the impacts of the COVID-19 pandemic on the health of people who experience imprisonment. Data sources We searched Medline, PsycINFO, Embase, the Cochrane Library, Social Sciences Abstracts, CINAHL, Applied Social Sciences Index and Abstracts, Sociological Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 76 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…During 2020, staff shortages, often resulting from pandemic-related illness, and constrained medical resources led to failures to meet the routine primary and specialty health care needs of incarcerated people ( 20 , 21 ). Pandemic-related mitigation policies and practices, including lockdowns and restricted movement, programming suspensions, visitor prohibitions, limited communication with loved ones, and solitary confinement in lieu of medical isolation, also increased stress, anxiety, and other mental health conditions ( 21 , 22 ). Moreover, the large number of causes of death reported as unknown suggests another systemic failure: inconsistencies and gaps in DOC reporting of mortality data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During 2020, staff shortages, often resulting from pandemic-related illness, and constrained medical resources led to failures to meet the routine primary and specialty health care needs of incarcerated people ( 20 , 21 ). Pandemic-related mitigation policies and practices, including lockdowns and restricted movement, programming suspensions, visitor prohibitions, limited communication with loved ones, and solitary confinement in lieu of medical isolation, also increased stress, anxiety, and other mental health conditions ( 21 , 22 ). Moreover, the large number of causes of death reported as unknown suggests another systemic failure: inconsistencies and gaps in DOC reporting of mortality data.…”
Section: Discussionmentioning
confidence: 99%
“…Second, prisons faced unprecedented constraints on their staff and their medical resources, limiting access to routine primary and specialty medical care and delaying the timely delivery of care (20), exacerbating the risk of deaths due to natural causes, including but not limited to COVID-19. Third, prisons imposed policies attempting to mitigate infection-such as lockdowns and restricted movements, programming suspensions, visitor prohibitions, limited communication with loved ones, and solitary confinement in lieu of medical isolation-all of which increased stress, mental health challenges, and violence (2,15,16,20,21,22,23), exacerbating the risk of deaths due to unnatural causes, such as drug overdoses, suicide, and violence.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Queen's University Belfast and UserVoice on the impact of prisoner lockdowns (User Voice & Queen's University Belfast, 2022) reported that ‘1 in 3 prisoners show symptoms of “severe anxiety disorder” indicating high levels of post‐traumatic stress’. When research and intervention delivery returned to prisons, we were entering a new environment; COVID‐19 had left major impacts on mental wellbeing and on relationships with prison staff (Kim et al., 2022). Specifically for the PROSPECT study, novel risk factors associated with suicide and self‐harm in prison seemed to have emerged, including fears among vulnerable prisoners because of the easing of restrictions.…”
Section: The Legacy Impact Of Covid‐19 Upon Prison‐based Health Researchmentioning
confidence: 99%
“…Previous studies have reviewed literature on the health impacts of COVID-19 in carceral settings (Kim et al, 2022) and outbreak management strategies for highly contagious diseases in prisons (Beaudry et al, 2020). A previously published systematic review of COVID-19 prevention strategies highlighted a dearth of data on vaccination and quarantine (Esposito et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Influenza outbreaks had very high attack rates in U.S. jails and prisons during the 1918 H1N1 virus (Kolata, 1999), 1957-1958 H2N2 virus (Cobos et al, 2016), 1968 H3N2 virus (Jester et al, 2020), and 2009 H1N1pdm09 virus (Reutter, 2010). Previous studies have reviewed literature on the health impacts of COVID-19 in carceral settings (Kim et al, 2022) and outbreak management strategies for highly contagious diseases in prisons (Beaudry et al, 2020). A previously published systematic review of COVID-19 prevention strategies highlighted a dearth of data on vaccination and quarantine (Esposito et al, 2022).…”
Section: Introductionmentioning
confidence: 99%